The Oil Price Volatility and a Revisited Saudi Import Demand Function: An Empirical Analysis - Algaeed, Abdulaziz Hamad (International Journal of Energy Economics and Policy, 2018)
The focus of this paper is to analyze theoretically and empirically the effects of a non-linear oil price shocks on Saudi import demand function covering the period of 1970-2015, utilizing unrestricted vector autoregressive (VAR) approach. Johansen’s testing procedure result asserts the existence of stable long-run relationship between real aggregate import demand (RIM), oil price shocks (OILPI and OILPD), real GDP, relative price and last year real foreign exchange (RFEt-1). The findings confirm that the oil price shocks affect negatively RIM. The signs are not as expected and significant. Moreover, the coefficients had little magnitude and effects. Nonetheless, the income elasticity is greater than one, had the right sign, and statistically significant. The price elasticity is negative as expected and significant. As predicted in literature, foreign exchange coefficient is negative, but is not statistically significant. Although the oil price shocks are significant, their magnitudes are weak. This could be attributed to the strong effects that come from traditional import demand determinants. Keywords: VAR, Import demand, Saudi Arabia, Income elasticity, and Co-integration. JEL Classifications: C51, E22, Q43. DOI: https://doi.org/10.32479/ijeep.6243